Active high-frequency acoustic thermometry of frozen water-saturated media - Yusupov, Vladimir I.; Semiletov, Igor P.; Chernykh, Denis V.; Salomatin, Aleksandr S. (Acoustical physics)
The article discusses promising method of active high-frequency acoustic thermometry, which measures the duration of the backscattering signal of ultrasonic pulses Delta t in the upper layer of water-saturated rocks or seabed sediments. An acoustic model is proposed to explain the strong temperature dependence of the duration of this signal in the region of zero and negative temperatures. It is shown that Delta t increases with decreasing temperature due to an increase in the reflection coefficient of ultrasonic waves from a layered structure and to a decrease in the absorption coefficient in a water-saturated medium. Field studies carried out on a vast area of the Arctic shelf confirmed the existence of such a dependence. The proposed approach can be effective for remote monitoring of temperature changes in frozen water-saturated rocks on land and in the upper layer of seabed sediments on the shallow Arctic shelf, which is necessary to estimate various environmental risks associated with global warming.